Study on The Effect of Annealing On The Optical Properties of The Pure Lead Sulfide (PbS) Films and Doping by Copper - WeÂ´am Sami; Amer Yassir (Al-Qadisiyah Journal of Pure Science, 2017)
Lead Sulfide (PbS) thin films were prepared by spraying pytolysis Method (SPM). Glass substrates with (1 x 2.6 x 7.6) cm were used at room temperature . Thin film of (PbS) was a doped by (Copper ,Cu) then the effect of annealing at different temperatures(100,200)C0 on the optical properties of (pbS) and (PbS:Cu) are investigation.The optical properties of the (pbs)and (pbs:cu) such as absorbance and transmittance have been analyzed by using (FTIR - 8400S) instrument. The optical band gab energy has been obtained from the plot between the (Î±hÏ…) as a function of photon energy (hÏ…) was (0.43) eV for (pbs) and (0.41 ) eV for (pbs:cu) at the room temperature . The absorption spectra of the films showed that (pbs) and (pbs:cu) have a direct band gap increase slowly with temperature annealing